2021
DOI: 10.3389/fonc.2021.683441
|View full text |Cite
|
Sign up to set email alerts
|

Laterally Extended Endopelvic Resection Versus Chemo or Targeted Therapy Alone for Pelvic Sidewall Recurrence of Cervical Cancer

Abstract: BackgroundLaterally extended endopelvic resection (LEER) has been introduced for treatment of pelvic sidewall recurrence of cervical cancer (PSRCC), which occurs in only 8% of patients with relapsed cervical cancer. LEER can only be performed by a proficient surgeon due to the high risk of surgical morbidity and mortality, but there is no evidence as to whether LEER is may be more effective than chemo or targeted therapy alone for PSRCC. Thus, we aimed to compare the efficacy and safety between LEER and chemo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(51 reference statements)
0
5
1
Order By: Relevance
“…Therefore, the decision for surgical excision in recurrent sarcoma should be appropriately made according to the surgeon's judgment in consideration of the histologic type and the extent of surgery. Third, tumors in the pelvic sidewall cause neuropathic pain due to sciatic nerve compression or irritation [27,38]. In this study, we found no statistically significant reduction in pain due to the small sample size.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Therefore, the decision for surgical excision in recurrent sarcoma should be appropriately made according to the surgeon's judgment in consideration of the histologic type and the extent of surgery. Third, tumors in the pelvic sidewall cause neuropathic pain due to sciatic nerve compression or irritation [27,38]. In this study, we found no statistically significant reduction in pain due to the small sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…In this study, we found no statistically significant reduction in pain due to the small sample size. However, in our previous study, we reported that LEER significantly reduced pelvic sciatic pain and morphine requirements in patients with recurrent cervical cancer compared to chemotherapy [27]. However, before surgery, 55.9% of patients complained of moderate to severe pain 10 with an NRS score of 4 or higher; after surgery, the pain intensity decreased to an NRS score of 3 or lower.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations